Effect of pH on activities of novel beta-lactamases and beta-lactamase inhibitors against these beta-lactamases. - Ohsuka, S (1995)
The effects of acidic conditions on activities of seven beta-lactamases--TEM-1 (class A), KOXY (class A), IMP-1 (class B), AmpC (class C), MOX-1 (class C), OXA-5 (class D), and PSE-2 (class D)--and their inhibitors were measured. The enzymatic activities of KOXY, IMP-1, and MOX-1 at pH 5.8 were slightly lower than those at pH 7.5. However, the activities of PSE-2 and OXA-5 were greatly reduced at pH 5.8. All of the beta-lactamase inhibitors tested had poorer inhibitory activities at pH 5.8 than at pH 7.5 except clavulanic acid for TEM-1.